Functional selectivity of insulin receptor revealed by aptamer-trapped receptor structures - Junhong Kim; Na-Oh Yunn; Mangeun Park; Jihan Kim; Seongeun Park; Yoojoong Kim; Jeongeun Noh; Sung Ho Ryu; Yunje Cho (Nature Communications, 2022)
DNA aptamers can activate insulin receptor as selective agonists or positive allosteric modulators. Here, authors determine structures of the insulin receptor bound to aptamers and provide a basis for the selective activation or allosteric regulation of insulin receptor.